2018
DOI: 10.18632/oncotarget.25292
|View full text |Cite
|
Sign up to set email alerts
|

PKD1 is a potential biomarker and therapeutic target in triple-negative breast cancer

Abstract: Protein Kinase D1 (PKD1) is a serine/threonine kinase encoded by the PRKD1 gene. PKD1 has been previously shown to be a prognostic factor in ERα+ tamoxifen-resistant breast tumors and PKD1 overexpression confers estrogen independence to ERα+ MCF7 cells. In the present study, our goal was to determine whether PKD1 is a prognostic factor and/or a relevant therapeutic target in breast cancer. We analyzed PRKD1 mRNA levels in 527 primary breast tumors. We found that high PRKD1 mRNA levels were significantly and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…PRKD1 overexpression helps to maintain cancer stemness through phosphorylation of protein kinase D/protein kinase C (PKD/PKCµ) and activation of the Wnt/β-catenin pathway [50]. Additionally, phosphorylated PKD/PKCµ has a negative effect on apoptosis through caspase-3 inhibition [51].…”
Section: Mir-34amentioning
confidence: 99%
See 1 more Smart Citation
“…PRKD1 overexpression helps to maintain cancer stemness through phosphorylation of protein kinase D/protein kinase C (PKD/PKCµ) and activation of the Wnt/β-catenin pathway [50]. Additionally, phosphorylated PKD/PKCµ has a negative effect on apoptosis through caspase-3 inhibition [51].…”
Section: Mir-34amentioning
confidence: 99%
“…However, the specific mechanism of PRKD1 remains unknown [50], and some research also indicates that PRKD1 has a contrary effect as a tumor suppressor or promoter in different cancer types [53]. For example, PRKD1 is expressed in normal ductal epithelial cells of the breast and inhibits EMT, which is a vital step for tumor cells to acquire the ability of invasion and metastasis [54].…”
Section: Mir-34amentioning
confidence: 99%
“…We previously demonstrated that PKD1 overexpression potentiates in vivo tumor growth of the MCF-7 adenocarcinoma-derived cell line, and regulates cell growth (Karam et al, 2012;Karam et al, 2014). Moreover, we identified PKD1 as a poor prognostic factor in the whole breast cancer population and in the triple-negative breast cancer (TNBC) subtype specifically (Spasojevic et al, 2018). Therefore, due to its crucial role in breast tumor growth and development, we asked in this study whether PKD1 may be a molecular target of BPA.…”
Section: Introductionmentioning
confidence: 99%
“… 6 - 8 Moreover, the previous study suggests that elevated tumor PKD1 expression independently predicts worse prognosis in patients with cancer. 9 Considering the regulation of PKD1 in the malignant progression of NSCLC, and its role as a biomarker in patients with cancer, we hypothesized that PKD1 might act as a potential biomarker in NSCLC. However, the clinical application of PKD1 in NSCLC largely remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%